The Challenges of Legal Protection on Traditional Cultural Expressions of Lampung - Rohaini Rohaini; Kingkin Wahyuningdiah; Nenny Dwi Ariani (Universitas Lampung, 2020)
Traditional Cultural Expressions are creations in the field of art that contain elements of traditional heritage characteristics as a national culture which are shared resources developed and maintained or preserved by certain traditional communities. In Lampung, there are various traditional cultural expressions of Lampung indigenous people that still exist. It needs to be protected due to it has unique characteristics and different from other intellectual works. Based on article 38 of Law No 14 of 2018 on Copyright, the Government of Lampung must protect and prevent unauthorized claims and misappropriation of Lampung Traditional Cultural Expression. Using the socio-legal approach, the reseach aims to examine and analyze kinds of legal protection done by Lampung Government for protecting TCE in Lampung, and the challenges of it.